The modular architecture of the neglect syndrome: Implications for action control in visual neglect - Coulthard, E; Parton, A; Husain, M (2007)
In our recent review of action control deficits in hemispatial neglect we concluded that many patients with the disorder have deficits in visuomotor control [Coulthard, E., Parton, A., and Husain, M. (2006). Action control in visual neglect. Neuropsychologia, 44(13), 2717-2733]. This conclusion has been questioned and it has been argued instead that there are no action deficits in neglect [Himmelbach, M., Karnath, H.-O., and Perenin, M.-T. (2007). Action control is not affected by spatial neglect: A comment on Coulthard et al. Neuropsychologia, 45(8), 1979-1981]. We proposed that rather than being specific to the neglect syndrome, action control deficits are more likely to relate to lesion location. Although many of these impairments may contribute to the manifestation of neglect, they may also occur in brain-damaged patients without the condition. In this article, we explore this framework further, discussing how neglect behaviour may emerge from damage to a set of visuomotor or cognitive modules, or their connections. Central to our view is the idea that the critical combination of deficits leading to neglect varies considerably between cases, and that visuomotor or cognitive modules disrupted in the syndrome may not, in fact, be specific to neglect. © 2007 Elsevier Ltd. All rights reserved.